2022
DOI: 10.1186/s12877-022-03285-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the correlation between frailty and sleep quality among elderly patients with osteoporosis: a cross-sectional study

Abstract: Background The incidence of osteoporosis increases with age. Frailty is a distinct characteristic seen in older osteoporosis patients. Poor sleep quality is common in elderly individuals. However, there are few studies on the correlation between frailty and sleep quality in elderly patients with osteoporosis in China. Methods This cross-sectional study was conducted from December 8, 2020, to April 30, 2021. A total of 247 patients who met the inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In this sense, poor sleep quality, defined by a PSQI above 5, was associated with increased odds for both frailty (OR = 1.78, 95% CI 1.19–2.66) and pre-frailty (OR = 1.51, 95% CI 1.20–1.90) [ 35 ]. Another study showed that a PSQI above 7 was associated with 2.68-fold increased odds of frailty (OR 2.68, 95% CI 1.04-6.91) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, poor sleep quality, defined by a PSQI above 5, was associated with increased odds for both frailty (OR = 1.78, 95% CI 1.19–2.66) and pre-frailty (OR = 1.51, 95% CI 1.20–1.90) [ 35 ]. Another study showed that a PSQI above 7 was associated with 2.68-fold increased odds of frailty (OR 2.68, 95% CI 1.04-6.91) [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that factors such as dietary structure, physical activity, smoking, and sleep quality are related to OP risk. For instance, a balanced diet [29] , adequate physical activity [25] , smoking cessation [30] , maintaining normal sleep [31] , and a normal BMI [28] are considered protective against OP and effective in reducing its risk.Our study adds to the existing literature by integrating these risk factors and exploring the relationship between LE8 and BMD. The results demonstrate a signi cant positive correlation between LE8 scores and BMD, especially notable in the high CVH group, emphasizing the importance of LE8 scores in monitoring BMD and highlighting the potential positive impact of modi able factors on BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Also, insufficient sleep or sleep deprivation may affect the central nervous system of the elderly through controlling of insulin metabolism and facilitation of insulin resistance (Jennings et al., 2007). Besides, the association for sleep problems and physical frailty is biologically plausible, and may be mediated by multiple factors, such as cardiovascular disease, depressive symptoms, lower testosterone levels, renal insufficiency, and higher levels of proinflammatory cytokines (Xu et al., 2022), whereas sleepiness and fatigue symptoms may be associated with premature brain atrophy and amyloid accumulation. Therefore, it would suggest programs, such as exercise or decompression activities (Kaur et al., 2019), to improve the quality of sleep and preventing cognitive decline in the elderly with sleep problems.…”
Section: Discussionmentioning
confidence: 99%